Microstructure and mechanical properties of functionally gradient cemented carbides fabricated by microwave heating nitriding sintering. (August 2016) - Tang, Siwen; Liu, Deshun; Li, Pengnan; Jiang, Lingli; Liu, Wenhui; Chen, Yuqiang; Niu, Qiulin
Abstract: A new method is presented for the fast preparation of functionally graded cemented carbide materials by microwave heating nitriding sintering. The influence of composition and sintering temperature on the mechanical properties, microstructure, and phase composition of the materials was studied. Results showed that functionally graded cemented carbides with the desired mechanical properties can be obtained rapidly by microwave heating nitriding sintering. A gradient layer with a Ti(C, N)-enriched surface layer, and underneath a Co-enriched layer formed on the top of the hard alloy substrate. The nitriding process had little effect on the microstructure of the matrix. A lower surface roughness, and the similar layer thickness as seen in conventional heating nitriding was obtained by microwave heating nitriding sintering in a short period of time. The thickness of the gradient layer increased with increasing temperature. The high Ti content in the raw material was beneficial to the formation of the gradient layer; however, the Co content had little effect on the gradient layer thickness when it increased from 6% to 10%. Highlights: A fast preparation method for functionally graded cemented carbides was proposed. A gradient TiCN-, Co-enriched layer sequence was formed on a hard alloy substrate. Layer thickness and surface roughness grew with Ti content and sintering temperature.